Peran Hubungan Masyarakat dalam Membangun Citra Positif Madrasah Aliyah Swasta Azzakariyah - Siti Raudhatul Jannah Siti Raudhatul Jannah; Atika Atika; Nur Padilah Nur Padilah (JMiE (Journal of Management in Education), 2024)
This study examines public relations management in enhancing the image of Madrasah Aliyah Swasta (MAS) Azzakariyah. The purpose of this research is to analyze how public relations are managed to build a positive institutional image. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The research subjects included the principal, vice principal for public relations, teachers, parents, and students. The findings reveal that improving the school’s image is essential to increase community satisfaction and create a positive impression, which contributes to students’ and alumni’s moral development and their integration into social, economic, and political life. Public relations management is carried out through three stages: (1) Planning, by collaborating with parents to establish an effective school image; (2) Implementation, through social engagement and cooperation with the community; (3) Evaluation, by conducting meetings with parents to resolve conflicts. The main factors supporting the enhancement of the school’s image are non-physical identity aspects, such as the school’s history, the reputation of its leadership, and students’ politeness in practicing the knowledge they have acquired.